2011
DOI: 10.1186/1471-2164-12-299
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression analysis supports a developmental model of low temperature tolerance gene regulation in wheat (Triticum aestivum L.)

Abstract: BackgroundTo identify the genes involved in the development of low temperature (LT) tolerance in hexaploid wheat, we examined the global changes in expression in response to cold of the 55,052 potentially unique genes represented in the Affymetrix Wheat Genome microarray. We compared the expression of genes in winter-habit (winter Norstar and winter Manitou) and spring-habit (spring Manitou and spring Norstar)) cultivars, wherein the locus for the vernalization gene Vrn-A1 was swapped between the parental wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 38 publications
(65 reference statements)
4
80
0
Order By: Relevance
“…The duration of LT tolerance is determined by the rate of phenological development and the time to vegetative/reproductive transition . The Vrn-A1 locus is a master switch for pathway that determines the vegetative/reproductive transition and directly influences the duration of LT tolerance Laudencia-Chingcuanco et al, 2011). Laudencia-Chingcuanco et al (2011) have shown that after vegetative/reproductive transition plant continues to lose ability to cold acclimate so that at 70 days after cold treatment the winter-habit genotypes were almost as cold sensitive as the untreated springhabit genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of LT tolerance is determined by the rate of phenological development and the time to vegetative/reproductive transition . The Vrn-A1 locus is a master switch for pathway that determines the vegetative/reproductive transition and directly influences the duration of LT tolerance Laudencia-Chingcuanco et al, 2011). Laudencia-Chingcuanco et al (2011) have shown that after vegetative/reproductive transition plant continues to lose ability to cold acclimate so that at 70 days after cold treatment the winter-habit genotypes were almost as cold sensitive as the untreated springhabit genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The Vrn-A1 locus is a master switch for pathway that determines the vegetative/reproductive transition and directly influences the duration of LT tolerance Laudencia-Chingcuanco et al, 2011). Laudencia-Chingcuanco et al (2011) have shown that after vegetative/reproductive transition plant continues to lose ability to cold acclimate so that at 70 days after cold treatment the winter-habit genotypes were almost as cold sensitive as the untreated springhabit genotypes. Bergjord et al (2008) have noticed a gradual decline of cold tolerance of winter wheat after December.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports describing de-acclimation and re-acclimation responses in perennial grass species [99][100][101][102][103][104][105], and some of them also report a negative association between freezing resistance and leaf growth during the de-acclimation period. In cereals, it has been shown that both freezing resistance and expression of cold-induced genes are down-regulated in shoot base tissue when the vernalization requirement is saturated, but before any development of the apex is visible in the microscope [106][107][108]. There is an interaction between vernalization and photoperiod on de-acclimation.…”
Section: Can We Increase Spring Productivity At High Latitudes?mentioning
confidence: 99%
“…Several studies indicate that there is a negative association between expression level of VRN1 and the expression of cold-induced genes and freezing resistance. Using near-isogenic lines of wheat and barley, and a T. monococcum deletion mutant, it was shown that, under 16 h photoperiod, the VRN1 locus controls expression of VRN1, COR14B, and other cold induced-genes [106][107][108]112,118]. High expression levels of VRN1 were associated with the down-regulation of cold-induced genes and freezing resistance.…”
Section: Regulation Of Leaf Growth Versus Freezing Resistance In Springmentioning
confidence: 99%